Religion And The Formation Of Israel Nation (Reflection For Christian Harmony) - Tirta Susila (Conference Series, 2020)
Paper gives an overview of the alliance of the tribes of Israel in building wholeness into a nation in the land of Canaan, how harmony is formed because there is a purpose and ideals that are pursued, and trusted. The tribes of Israel were united by belief in one God, which made them able to get along well. This can provide motivation for Christians today. Christians are called to live in fellowship with Christ and others. The fellowship is also the basis of harmony for Christians. The description of the entry to the land of Canaan, about the pattern of lives, both socially political and religiouses, that initially consisted of tribes later constituted a "national unity & quot;. Paper uses qualitative research methods are library research. According to Sugiyono, literature study deals with theoretical studies and other references relating to values, culture and norms that develop in the social situation under study.